Analogies à visée argumentative dans les romans graphiques traitant de la Shoah - Silvia Adler (Argumentation et Analyse du Discours, 2023)
This paper examines the functioning of analogies in comics and graphic novels as a multimodal medium, and more particularly in graphic novels dealing with the Holocaust. Two questions will be addressed in the present study: (a) what triggers the argumentative effect of these analogies and how do they participate in the construction of an argument? (b) what singularizes arguments from analogy constructed in the “sequential art”?